HUBUNGAN PEKERJAAN DAN RIWAYAT PERSALINAN PRETERM DENGAN KEJADIAN PERSALINAN PRETERM DI RSUD Prof. Dr. MARGONO SOEKARDJO PURWOKERTO - Anasari, Tri; Pantiawati, Ika (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Preterm delivery is not old enough labor below 37 weeks gestation and birth weight less than 2500 gram. The impact that may result from the incidence of preterm labor include hypothermia, asphyxia, jaundice, infections and fetal growth retardation. The impact is a major cause of death in infants. Preterm labor in hospitals MargonoSoekarjo of the year 2010- 2013 continues to increase. The Year 2011 increased 0.01%, in 2012 rose 3.32% and in 2013 increased by 3.4%. The purpose of this study was to determine the employment relationship and a history of preterm labor with the incidence of preterm labor in hospitals Prof. Dr. MargonoSoekarjoPurwokerto. This type of research is analytic survey with a retrospective case control approach. The study population was all women giving bith from January to December 2013. The sample in this study amounted to 77 preterm birth mothers and 77 non preterm birth mothers with a total of 154 respondents, using systematic random sampling technique. Bivariate analysis using chi square test and multivariate analysis using logistic regression. Results: Most of employment were not at risk as much as 87 (56,5%) and a history of preterm labor were not at risk as much as 101 (65,6%). There is an employment corelation with the incidence preterm labor (p = 0.000), there is a history of preterm labor corelation with the incidence preterm labor (p = 0.000). Conclusion: there is a corelation of employment and history of preterm labor with the incidence of preterm labor in hospitals Prof. Dr. MargonoSoekarjoPurwokerto. Keywords: Preterm Labor, Employment, Historyof preterm labor